THE INFLUENCE OF SOCIAL MEDIA MARKETING, E-WOM AND BRAND AWARENESS ON PURCHASE INTENTION AT UNIQUESHOP.IND JEWELLERY ONLINE SHOP - Eunike Lumingkewas; Willem J. F. A. Tumbuan; Merinda H. C. Pandowo (Universitas Sam Ratulangi, 2023)
This study investigates the relationships between social media marketing (SMM), electronic word of mouth (eWOM), brand awareness, and their influence on purchase intention as the dependent variable. In the digital age, where consumers are increasingly exposed to various marketing stimuli, understanding the drivers of purchase intention is crucial for businesses and marketers. The researcher conducted this research through quantitative methods, data was collected through an online questionnaire with a purposive sampling technique with criteria of who have followed Uniqueshop.ind on Instagram, observed their social media marketing activities, female or male (15-50 years old) and have income. The total sample size consisted of 100 respondents. Multiple Regression Analysis method is used to analyze the influence of the independent variables toward the dependent variable. The results of this study indicate that Electronic Word of Mouth and Brand Awareness have a positive and significant influence on Purchase Intention, while Social Media Marketing does not have a significant direct influence on Purchase Intention partially. The results also indicate that Social Media Marketing, Electronic Word of Mouth and Brand Awareness simultaneously influence Purchase Intention positively and significantly. Keywords: social media marketing, electronic word of mouth, brand awareness, purchase intention